Clinical pathogenic basis for anti-adhesive treatment for appendicular-genital syndrome in women of reproductive age - V.V. Simrok; I.A. Popova; M.A. Melnikova (LCC «Medicine-Inform», 2020)
V.V. Simrok1, I.A. Popova2, D.V. Mel'nikova3 1Rostov State Medical University, Rostov-on-Don, Russian Federation 2St. Luca Lugansk State Medical University, Lugansk, Lugansk People's Republic 3LLC "MedFormula", Sevastopol, Russian Federation Aim: to assess the efficacy of penicillamine for the complex prevention of pelvic peritoneal adhesions in appendicitis associated with the acute conditions of uterine appendages (appendicular-genital syndrome, AGS) based on the changes in the levels of hydroxyproline and the major clinical symptoms of pelvic inflammatory disease. Patients and Methods: 157 women of reproductive age with AGS who were urgently or routinely admitted to a gynecological or surgical hospital were examined. Comparison group women were prescribed with conventional anti-inflammatory treatment or surgery as needed. Study group women additionally received penicillamine 250 mg twice daily for a month. Pre- and post-treatment non-invasive assessment of the peritoneal adhesive process was performed by measuring the levels of protein-bound and free hydroxyproline. Treatment efficacy was evaluated after 1 month by the changes in hydroxyproline levels, major clinical symptoms, and ultrasound. Results: it was demonstrated that pelvic acute inflammatory disease results in > 1.5-fold increase in the levels of protein-bound and free hydroxyproline. Penicillamine as a component of the complex treatment for pelvic inflammatory disease reduces the levels of hydroxyproline to normal ranges. The changes in the major clinical symptoms and ultrasonic findings after penicillamine therapy were more significant compared to the standard treatment. Conclusions: penicillamine as a component of the complex treatment for pelvic inflammatory disease significantly accelerates the improvement of symptoms and remission as well as the formation of peritoneal adhesions. This prevents both pelvic adhesive disease and tubal- and peritoneal-factor infertility. Keywords: appendicular-genital syndrome, inflammation, hydroxyproline, penicillamine, pelvic peritoneal adhesions, prevention, adhesion formation. For citation: Simrok V.V., Popova I.A., Mel'nikova D.V. Clinical pathogenic basis for anti-adhesive treatment for appendicular-genital syndrome in women of reproductive age. Russian Journal of Woman and Child Health. 2020;3(4):228-232. DOI: 10.32364/2618-8430-2020-3-4-228-232.